O desafio da gestão de dados de pesquisa em instituições de ensino superior públicas brasileiras: diretrizes para o desenvolvimento de uma política institucional - Araújo, Ana Lúcia da Silva (2023)
This study covered the global evolution of data sharing in research, emerging the need to manage these data in an organized and responsible way. With the conviction that an institutional policy for research data management is essential to establish mandatory and standardized practices, this research sought the crucial elements and approaches to enable such services. The presentation of the results was based on an investigation of the literature in the area, legal and institutional documents, guidelines and standards of national and international specialized organizations, conducted through a qualitative, exploratory and applied research methodology. In order to understand the scope and gaps in the national scenario in relation to the topic, information was collected from brazilian universities, as well as from other institutions with which they are related, such as research institutes and funding agencies. To achieve the main objective of this research, research data management policies in countries that already have established policies were analyzed, in which education and research institutions served as reference models. Among these, the universities of the Netherlands, recognized for their commitment to the principles of Open Science, were chosen to extract elements and approaches from their documents. Through individual and comparative analyzes, a spreadsheet was developed to identify the common and singular elements of these policies. From this, a framework was constructed with possible guidelines and approaches that can be applied in the construction of policies for teaching and research institutions in Brazil. It was found that there are significant differences between the two countries in terms of support from government institutions, infrastructure, national-level regulations and federated services to enable and support services. It was concluded that the development of institutional policies and data management in Brazilian universities lack support from government institutions, knowledge and recognition of the value of research data from their institutional leaders.